INTERNATIONAL LEGAL ASSURANCE OF PEACE AND SECURITY: CONCEPT AND MEANS OF ACHIEVEMENT - Husar, Olga; Olkhovik, Myroslava (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is to study the subject matter and sources of international legal peace and security, to analyze the means of international dispute resolution, and to investigate Ukraine’s security priorities in times of war. Research methods: the chosen topic of research requires the use of various scientific methods and approaches to obtain high-quality results. Therefore, to solve the tasks, we used the following research methods: analysis - study of modern scientific approaches to the study of "international security"; systematic method helped to carry out a comprehensive analysis of the features of international legal documents on international security issues; analytical method provided an opportunity to analyze the state of cooperation between Ukraine and European security structures. Results: in accordance with the principles of international law, the structure of the international system and, ultimately, international relations themselves, different concepts of international security have been formed. All of them are based on scientific considerations, explain international processes, and are capable of making certain predictions about the future. At the same time, as we have noted, these concepts contain specific methods and means of ensuring international security. Among the most popular concepts are balance/balance of power, global/common/comprehensive security, collective security, cooperative security, as well as hegemonic stability, balance of threats, and peaceful coexistence. They are based on different principles: balance of power, hegemony, balance of interests, etc. Discussion: defining the essence of modern threats and challenges helps to determine the methodology for substantiating the tasks of ensuring international security in general, as well as the security of the state of Ukraine in particular, and to develop a regulatory framework for ensuring peace and security in the world.